Structural Reform in Germany - Krebs, Tom.; Scheffel, Martin (Washington, D.C. : International Monetary Fund, 2016)
This paper provides a quantitative evaluation of the macroeconomic, distributional, and fiscal effects of three reform proposals for Germany: i) a reduction in the social security tax in the low-wage sector, ii) a publicly financed expansion of full-day child care and full-day schooling, and iii) the further deregulation of the professional services sector. The analysis is based on a macroeconomic model with physical capital, human capital, job search, and household heterogeneity. All three reforms have positive short-run and long-run effects on employment, wages, and output. The quantitative effects of the deregulation reform are relatively small due to the smal size of professional services in Germany. Policy reforms i) and ii) have substantial macroeconomic effects and positive distributional consequences. Ten years after implementation, reforms i) and ii) taken together increase employment by 1.6 percent, potential output by 1.5 percent, real hourly pre-tax wages in the low-wage sector by 3 percent, and real hourly pre-tax wages of women with children by 2.7 percent. The two reforms create fiscal deficits in the short run, but they also generate substantial fiscal surpluses in the long-run. They are fiscally efficient in the sense that the present value of short-term fiscal deficits and long-term surpluses is positive for any interest (discount) rate less than 9 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet